Musalogue (a catalogue of Musa germplasm): Diversity in the genus Musa - Daniells, J.; Jenny, C.; Karamura, D.; Tomekpe, Kodjo (International Network for the Improvement of Banana and Plantain, 2001)
The first part of this publication (loose-leafed, in a file) describes wild Musa species. In the second part the focus is on cultivated varieties, particularly two important cultivar groups - East African Highland bananas and the true plantains. For each entry there is a photograph and a morphological description.